Pengelolaan Pemasaran Pendidikan Berbasis Teknologi Informasi pada Masa Pandemi Covid-19 di SMA Nurul Iman Palembang - Bella; Ahmad Zainuri; Dian Safitri (JMiE (Journal of Management in Education), 2021)
This research aims to find out the process of managing information technology-based educational marketing during the covid-19 pandemic. The study uses qualitative descriptive methods with data collection techniques using observations, interviews, and documentation. Data analysis uses data reduction, data presentation, and conclusion withdrawal. The results showed that information technology-based education marketing management was carried out by implementing management functions including planning, organizing, implementation, and supervision. Principals and teachers manage the marketing process using information technology developed through online media such as Facebook, Instagram, and the school's official website. The school also cooperates with infokom parties to disseminate educational marketing in creative ways.